An integrated approach to tackling wildlife crime: Impact and lessons learned from the world's largest targeted manta ray fishery. Issue 2 (10th December 2020) - Booth, Hollie; Mardhiah, Ulfah; Siregar, Hanifah; Hunter, Jonathan; Giyanto,; Putra, Mochamad Iqbal Herwata; Marlow, Jo; Cahyana, Andi; Boysandi,; Demoor, Apolinardus Yosef Lia; Lewis, Sarah; Adhiasto, Dwi; et al.
Abstract: Manta rays ( Mobula birostris and M. alfredi ) are threatened by overexploitation for international trade. Indonesia was home to the world's largest documented manta fishery—Lamakera, in East Nusa Tenggara. However, in 2014, the Indonesian government declared manta rays a protected species. Here we describe an integrated intervention to reduce manta hunting and mortality in Lamakera, which combined community outreach and livelihood‐focused incentives with targeted enforcement actions; and assess its impact over a five‐year period (2013–2018) using a theory‐based research design. Results show that the intervention is associated with a significant decline in manta hunting effort and mortality ( p < .001), which is correlated and temporally‐associated with conservation activities, and did not occur for modeled and natural experiment counterfactuals. Overall, total manta ray mortality declined by 86% by 2018, vs. the 2013 baseline. We conclude that a multifaceted, data‐driven approach reduced illegal hunting and trade of manta rays from 2013 to 2018. However, this impact is not indefinite; new challenges are emerging, which highlight the importance of a long‐term adaptive strategy. We make several recommendations for designing interventions to mitigate trade‐driven over‐exploitation of megafauna: (a) understand diverse drivers of human behavior; (b) adopt data‐driven problem‐oriented planning; (c) continuously document and share learning; (d) establish partnerships with diverse stakeholders to develop resilient institutions for enduring impact.